Workshop on Capacity Building for Healthcare Workers in the Rapid Management of Severe Head Trauma Patients in Primary Healthcare Facilities - Hardianti, Siti (JURNAL PENGMAS KESTRA (JPK), 2024)
Severe head trauma is a medical emergency requiring rapid and appropriate management to prevent disability and mortality. Healthcare workers in primary healthcare facilities often serve as the first responders in managing patients with severe head trauma. Therefore, systematic training to enhance their capacity is essential. Objective: This workshop aims to improve the knowledge and skills of healthcare workers in the rapid and effective management of severe head trauma patients in primary healthcare facilities. Methods: The workshop was conducted using a blended approach, including theoretical sessions, simulation-based practice, and case studies. Participants included doctors, nurses, and other healthcare professionals working in primary healthcare facilities. Evaluation was carried out through pretests and posttests to measure knowledge improvement, as well as observational assessments of participants' skills in clinical simulation scenarios. Results: The workshop significantly enhanced healthcare workers' understanding and skills in managing severe head trauma patients. The evaluation results indicated a notable increase in participants' average scores from pretests to posttests. Additionally, simulation practices demonstrated improvements in initial patient assessment, condition stabilization, and appropriate referral procedures. Conclusion: This workshop effectively enhances the capacity of healthcare workers in the rapid management of severe head trauma patients in primary healthcare settings. It is recommended that similar training programs be conducted regularly to improve the quality of emergency care at the primary level.